Contribution of Character Strengths to Psychology Stress, Sleep Quality, and Subjective Health Status in a Sample of Chinese Nurses - Zhang, Shu-e; Yang, Li-bin; Zhao, Chen-xi; Shi, Yu; Wang, Hong-ni; Zhao, Xin; Wang, Xiao-he; Sun, Tao; Cao, De-pin (Frontiers in Psychology, 2021)
Objectives: The main objectives of this study were to describe the current state of character strengths (CSs) of nurses; explain how they affect stress, sleep quality, and subjective health status; and reveal the mediating role of stress for the subject matter on the association between CSs, sleep quality, and subjective health status. Methods: A cross-sectional online survey was conducted from September to October 2020 in China. A multistage stratified sampling method was used, and 1,221 valid questionnaires across 100 cities in 31 provinces were collected. Results: For the participants in this survey, the three dimensions of CSs ranging from high to low were caring (4.20 ± 0.640), self-control (3.53 ± 0.763), and inquisitiveness (3.37 ± 0.787). There was difference in CSs scores across age (F = 8.171, P < 0.01), professional categories (F = 5.545, P < 0.01), and job tenure (F = 9.470, P < 0.01). The results showed that CSs significantly affected the psychological stress (β = −0.365, P< 0.01), sleep quality (β = 0.312, P< 0.01), and subjective health (β = 0.398, P< 0.01) of nurses. Moreover, psychological stress partially mediated the association between CSs and both types of health outcomes. Conclusion: In China, the CSs of nurses are at high levels. We find that nurses with high-level CSs are likely to experience less psychological stress and exhibit healthy psycho–physiological responses, which contribute to positive health outcomes. Finally, our study argues that strength-based interventions of positive psychology in hospitals should be provided to minimize threats to the physical and psychological health of health professionals, which is a beneficial choice for future hospital reforms in the domain of occupational health management.